HumAnimal : Race, Law, Language - Seshadri, Kalpana (Book collections on Project MUSE., 2011)
HumAnimal explores the experience of dehumanization as the privation of speech. Taking up the figure of silence as the space between human and animal, it traces the potential for an alternate political and ethical way of life beyond law. Employing the resources offered by deconstruction as well as an ontological critique of biopower, Kalpana Rahita Seshadri suggests that humAnimal, as the site of impropriety opened by racism and manifested by silence, can be political and hazardous to power.